KRITIK NALAR BERAGAMA DALAM NOVEL TUHAN, IZINKAN AKU MENJADI PELACUR KARYA MUHIDIN M. DAHLAN - Ambali Wijaya; Tirta Alim Wiliam Diaz (Journal of Applied Transintegration Paradigm, 2025)
This research is motivated by the anxiety in the author's mind, which in the novel Muhidin M. Dahlan, Nidah Kirani's religious reasoning needs to be criticized philosophically so that religious reasoning does not go wrong, in Indonesia the Ministry of Religion Nasarudin Umar strongly encourages religious moderation so that in carrying out religious practices there is no fanaticism like that done by the main character in the novel Tuhan, Izinkan aku menjadi pengacur. The research approach used by the author is qualitative research with a library research model (library research) in this thesis the researcher uses the theory of religious moderation indicators, namely National Commitment, Tolerance, Anti-violence and Accommodating to local culture so that it is easy to examine Nidah Kirani's Reasoning, This research also uses a philosophical review, so that this research study is in-depth to its roots, so that it is easy to see Nidah Kirani's religious reasoning in the novel Tuhan, Izinkan Aku Menjadi Pelacur. The results of this study indicate that Nidah Kirani's reasoning in the novel Tuhan, biar aku menjadi perempuan contains 32 religious reasons consisting of four aspects, namely tauhid, muamalah, sharia, and worship. Of these four aspects, Nidah Kirani's reasoning is not in accordance with the theory of religious moderation in the sense that Nidah Kirani's reasoning is a fanatical religious reasoning.